Translation of hardness numbers in testing of surface‑hardened steel products - A. L. Valko; S. P. Rudenko; S. G. Sandomirski (Литьë и металлургия)
Recalculation formulae of hardness transformation in units of HRC into Vickers hardness HV 30 for hardened and tempered structural steels in ASTM E 140-07 and ISO 18265:2013 were analyzed. From a Vickers hardness reading of 62.3 HRC using a 4.903 N indenter, the hardness is converted to 294.2 N and the hardness is converted to HRC using the ASTM E 140-07 formula. Full agreement of average hardness value HRC with reference measure is obtained. Correction factor of conversion to hardness at 294,2N and approximating relationship between hardness value HV0,2 and hardness value measured at 4,903N load during testing is given. The relationship between Vickers hardness HV, HV0.5, HV0.2 and hardness in units of HRC for hardened and tempered structural steels is given.